CAPM LQ 45 Analysis on IDX: Comparison Between the Property & Building Sector and the Agricultural Sector Before COVID-19 - Silalahi, Pristanto (Enrichment : Journal of Management, 2025)
This study maps the risk and returns with the CAPM approach, looking at stock issuers and comparing the property with agricultural sectors. The aim is to dig deeper into the differences in risk and return faced by these two sectors. In addition, this study has practical value for investors who want to mitigate risk and optimize portfolios and for decision makers who need to consider which sectors are more vulnerable to economic changes. The property sector and the agricultural sector behave quite differently in changing market conditions during the observation period. Based on empirical testing, it was found that stocks in the property and building sector are aggressive compared to the share in the sector of Agriculture. This is seen from each shared sample research's mark beta (β). Ultimately, these findings can help manage portfolios with more measurable risks